Changes of retinal and choroidal capillary blood flow in macula after an acute intraocular pressure elevation. Issue 26 (26th June 2020) - Ma, Ziwei; Pan, Xuefeng; Zhou, Danni; Zhu, Zhuangzhi; Xu, Aiping; Shi, Peng; Chen, Hong
Abstract : Abstract: The aim of this study was to investigate the changes of retinal vessel density (VD) and choriocapillary blood flow area (CBFA) in macula after an acute intraocular pressure (IOP) elevation observed using optical coherence tomography angiography. This was a prospective comparative study of subjects with narrow anterior chamber angles who underwent laser peripheral iridotomies (LPIs). The IOP was measured before and 1 hour after the LPI. The retinal VDs and CBFAs of the macula were measured using optical coherence tomography angiography at the baseline and 1 hour after the LPI. A total of 88 eyes of 88 individuals were enrolled in our study, and 70 eyes of 70 individuals finally completed the study with a mean IOP rise of 10.2 ± 7.5 mm Hg after the LPI. The VDs and areas of foveal avascular zone of all of the subjects did not differ significantly between the measurements obtained at the baseline and 1 hour after the LPI ( P  > .05). However, there were statistically significant differences in the CBFAs at the baseline and 1 hour after the LPI ( P  < .05). Based on the magnitude of the rise in the IOP, we divided the subjects into three groups: group A = IOP rise ⩽ 10 mm Hg, group B = 10 mm Hg < IOP rise ⩽20 mm Hg, and group C = IOP rise > 20 mmHg. The VDs of the macula measured at the baseline were significantly different from the measurements obtained 1 hour after the LPI in group C in either the superficial retinal layer or deep retinal layer ( P  < .05). Compared with baseline, the CBFAs measured at 1 hour after the LPI were decreased in group B and group C ( P  < .05). In these subjects with narrow antenior chamber, the blood flow in macula began to be affected with the acute IOP rise greater than 10 mm Hg. It was confirmed that the retina and choroid showed some different ability to regulate its blood flow in response to changes in IOP.